MANAGEMENT OF STRESS AND MOTIVATION OF EMPLOYEES - UNNIKRISHNAN (International Journal of Research -GRANTHAALAYAH, 2015)
Stress is a physical and emotional reaction when everyone encounters the various challenges of life. It will lead to mental unrest.Stress is the body’s automatic response to any physical or mental demand placed on it. Stress is a negative concept and creates a negative mental attitude in the mind of individuals. The various reasons for stress in organizations are over work load, role ambiguity, role conflict, isolation, lack of family-social support etc. Moderate stress relating to job aspects is essential because it helps to improve the performance of employees. But over stress leads to mental dissatisfaction, conflict, absenteeism, turnover etc.so every organizations must care their employees from having over stress. Division of work, prioritizing & organizing, yoga &meditation, balanced time schedule, improving emotional intelligence etc are some of the ways to minimize stress .The concept of motivation can be effectively used to remove stress from our organization .Different motivational techniques such as financial incentives, appreciation, personal encouragement,training and development programs ,seminar & workshops etc. will helps to throw away stress from organizations , if complete stress had been removed ,and motivation is given , a complete & strategic organizational change will takes place in organization..